2017
DOI: 10.1093/mnras/stx015
|View full text |Cite
|
Sign up to set email alerts
|

Precise strong lensing mass profile of the CLASH galaxy cluster MACS 2129

Abstract: We present a detailed strong lensing (SL) mass reconstruction of the core of the galaxy cluster MACS J2129.4−0741 (z cl = 0.589) obtained by combining high-resolution Hubble Space Telescope photometry from the CLASH (Cluster Lensing And Supernovae survey with Hubble) survey with new spectroscopic observations from the CLASH-VLT (Very Large Telescope) survey. A background bright red passive galaxy at z sp = 1.36, sextuply lensed in the cluster core, has four radial lensed images located over the three central c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 33 publications
11
50
0
Order By: Relevance
“…Using data for clusters at z ∼ 0.2 observed with the CFH12k instrument on the Canada-Hawaii-France Telescope (CFHT), Limousin et al (2007) arrived at a similar conclusion. Halkola et al (2007) and Suyu & Halkola (2010) used strong lensing measurements of a single cluster and a small galaxy group, respectively, and also found evidence for strong truncation of the density profiles of satellite galaxies, and other strong lensing studies have reached similar conclusions (e.g., Eichner et al 2013;Monna et al 2015Monna et al , 2017. Likewise, Okabe et al (2014) analyzed the weak lensing signal of subhaloes in the Coma cluster and found that, while group-scale subhaloes show (mild) evidence of sharp truncations at radii r < 200 kpc, stacked weak lensing measurements of satellite galaxies show no signs of truncation.…”
Section: Introductionmentioning
confidence: 64%
“…Using data for clusters at z ∼ 0.2 observed with the CFH12k instrument on the Canada-Hawaii-France Telescope (CFHT), Limousin et al (2007) arrived at a similar conclusion. Halkola et al (2007) and Suyu & Halkola (2010) used strong lensing measurements of a single cluster and a small galaxy group, respectively, and also found evidence for strong truncation of the density profiles of satellite galaxies, and other strong lensing studies have reached similar conclusions (e.g., Eichner et al 2013;Monna et al 2015Monna et al , 2017. Likewise, Okabe et al (2014) analyzed the weak lensing signal of subhaloes in the Coma cluster and found that, while group-scale subhaloes show (mild) evidence of sharp truncations at radii r < 200 kpc, stacked weak lensing measurements of satellite galaxies show no signs of truncation.…”
Section: Introductionmentioning
confidence: 64%
“…The input cosmology was also revealed. We refer the reader to Meneghetti et al (2016) for a detailed presentation on how Ares and Hera mass distributions were generated, here we only present a quick overview.…”
Section: The Datamentioning
confidence: 99%
“…MNRAS 000, 1-19 (2017) (Navarro et al 1997) or Hernsquist (Hernquist 1990). For instance, large-scale potentials are modelled with either a NFW or PIEMD, BCGs with PIEMD or Hernquist profiles and individual clusters members with a PIEMD profile, scaled according to the relations in Limousin et al (2005).…”
Section: Mass Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…To disentangle the cluster-scale dark halo component from the galaxies' contribution, additional constraints sensitive to only one of the two components are necessary (Eichner et al 2013;Monna et al 2015). A common assumption is that the DM content of galaxies scales in proportion to their light (e.g.…”
Section: Introductionmentioning
confidence: 99%